Membangun Kepemimpinan yang Efektif di Sekolah dengan Pendekatan Psikologi Manajerial - Muhammad Fikri Firmansyah; Kanzul Aras Nurjannah; Elfa Mazroatul Mawaddah; Fajar Zikri Ramdhan Cahyadi; Mu’alimin Mu’alimin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Building effective leadership in schools is key to creating a productive and harmonious educational environment. A managerial psychology approach can provide in-depth insight into effective ways of leading, by considering psychological aspects that influence individual behavior and performance in school organizations. This approach focuses on understanding the psychological characteristics of leaders and team members, managing emotions, and effective communication in building mutually supportive relationships. In an educational context, managerial psychology can help school leaders to manage team dynamics, increase motivation, and create a positive work climate. Therefore, it is hoped that the application of managerial psychology principles in leadership in schools can produce more effective school management, both in the aspects of teaching, management and human resource development.